Reading architecture : a visual lexicon - Hopkins, Owen, 1984- (Laurence King, 2012)
This innovative and unique book is a visual guide to the buildings that surround us, naming all the visible architectural features so that, unlike other architectural dictionaries, the reader doesn't have to know the name before looking it up. Clear line drawings and extensive colour photographs illustrate each of the main building types, from forts to churches, stately homes to skyscrapers. The individual structural elements and materials common to all buildings are then explained, whether in Classical, Gothic or Modernist style, before delving into the inner architectural details such as doors and windows, roofs and staircases. A comprehensive glossary completes the book. An original and accessible take on the architectural dictionary, this book takes you on a visual tour of the buildings around us, and will be useful not only to students but to anyone with a general interest in architecture.